Self-Regulation as a Basic Element of the Professional Culture of Engineers - Maria Odinokaya; Tatyana Krepkaia; Irina Karpovich; Tatiana Ivanova (MDPI AG, 2019)
This paper addresses the problem of the formation of the self-regulation of educational activities of students studying in a technical university. The purpose of this paper is to discuss the problem of the self-regulation of educational activities of students, presenting data from an experimental study of students’ self-regulation. Special attention is paid to the distinction between the terms self-control and self-regulation. This paper presents data on the state of self-regulation among students studying technical specialties. The research methodology is based on the theoretical analysis of the results of scientific works, which present the main provisions on the formation of students’ self-regulation. The research methods include questioning and a methodical experiment. The stages of the formation of students’ self-regulation are highlighted, and the main directions of teachers’ work on the formation of students’ self-regulation are determined. The structure of self-regulation is described and the condition for its formation is justified using the technology of self-regulation formation. Based on the study, students’ self-regulation is linked to the awareness of their professional and personal goals, as well as to the level of regulatory and reflective qualities. Personal and professional self-improvement in the process of vocational education depends on the level of the formation of regulatory and reflexive qualities.